Control of Fusarium Disease in Onion with Plant Growth Promoting Rhizobacteria (PGPR) and Mycorrhizae and Its Effect on Growth and Yield of Onion - Salamiah Salamiah; Muhammad Anton Ciptady; Chatimatun Nisa (Journal of Wetlands Environmental Management, 2019)
The productivity of onion in Indonesia is generally low due to fusarium wilt disease.Â  Biological controls can be applied using PGPR and Mycorrhizae. The purpose of this research was understand the interaction between PGPR and Mycorrhizal inoculation against fusarium wilt intensity as well as the growth and yield of onions. The isolation of Fusarium oxysporum f.sp cepae and PGPR, followed by the tests of PGPR inhibition ability, phosphate solvent and HCN compound productivity. The method used in the field was a completely randomized design (CRD) with 2 replications. Results showed that the combination of PGPR and mycorrhizae as a whole was unable to suppress Fusarium wilt disease, but had significant effect to postpone the incubation period (26,19 days after inoculation) and increase the growth and yield of onion compared to the onion plants infected with Fusarium but without the combined treatment of PGPR and mycorrhizae and the PGPR treatment and mycorrhizal treatment as single treatments; the application of mycorrhizae as the single factor had a very significant effect on the number of bulbs, but had no significant effect on the inhibition of fusarium wilt intensity as well as the growth and yield of onions.